2019
DOI: 10.1111/adb.12746
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging and motor control deficits are related to regional deformation of central cerebellar white matter in alcohol use disorder

Abstract: The World Health Organization estimates a 12-month prevalence rate of 8+% for an alcohol use disorder (AUD) diagnosis in people age 15 years and older in the United States and Europe, presenting significant health risks that have the potential of accelerating age-related functional decline. According to neuropathological studies, white matter systems of the cerebellum are vulnerable to chronic alcohol dependence. To pursue the effect of AUD on white matter structure and functions in vivo, this study used T1-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…Irle and Markowitsch (1983) showed that both PTD treatment and long‐term EtOH exposure (30% EtOH; 20 months) cause damage to cerebellar Purkinje cells and shrinkage of the granular layers of the vermis. Previous imaging studies in humans also found cerebellar atrophy, including white matter, which was associated with deficits in motor control and memory (Kril and Harper, 2012; Zhao et al, 2020). Although the cerebellum proved to be an area of increased susceptibility to both EtOH toxicity and thiamine deficiency, our findings revealed that myelin‐related gene expression in the cerebellum varied as a function of recovery time from both moderate and severe thiamine deficiency treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Irle and Markowitsch (1983) showed that both PTD treatment and long‐term EtOH exposure (30% EtOH; 20 months) cause damage to cerebellar Purkinje cells and shrinkage of the granular layers of the vermis. Previous imaging studies in humans also found cerebellar atrophy, including white matter, which was associated with deficits in motor control and memory (Kril and Harper, 2012; Zhao et al, 2020). Although the cerebellum proved to be an area of increased susceptibility to both EtOH toxicity and thiamine deficiency, our findings revealed that myelin‐related gene expression in the cerebellum varied as a function of recovery time from both moderate and severe thiamine deficiency treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Neuroradiologically, the mainstay of studies of uncomplicated Alcohol Use Disorder (AUD) concurs with neuropathological findings, which are typically more prominent in white than gray matter (Monnig et al, 2013; Sawyer et al, 2016; Zhao et al, 2019). Quantitative MRI studies report tissue shrinkage typically in the anterior superior vermis, involving regions I-V with additional sites of volume deficits in gray matter (Le Berre et al, 2014; Ritz et al, 2016; Sullivan et al, 2000) and white matter (Sawyer et al, 2016; Sullivan et al, 2000; for review, Zahr and Pfefferbaum, 2017) of the cerebellar hemispheres, also exacerbated by common alcoholism-related concomitant complications (Ritz et al, 2016; Sullivan et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…The anterior deficits would be predicted from other studies of alcoholism, and the posterior and inferior regions would be predicted from a recent analysis of the corpus medullare. Specifically, use of a novel Jacobian deformation morphology approach to quantify the total corpus medullare of the cerebellum revealed AUD-related volume deficits and accelerated aging in the total corpus medullare and regional shrinkage of surfaces adjacent to lobules I-V, IX, and X (Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, heavy drinking is associated with aggressive behavior, intimate partner violence, economic hardship, and job loss [ 47 49 ], all of which predict both suicide and alcohol-related deaths [ 50 52 ]. Of particular concern in older adults for whom physical illness and disability constitute a major risk factor for suicide [ 53 56 ], chronic AUD can also accelerate aging processes [ 57 , 58 ] and produce toxic physiological effects [ 59 ]. Moreover, cognitive deficits that emerge from repeated alcohol misuse may impair emotion regulation, decision-making and behavioral control [ 60 ], contributing to increased suicide risk [ 61 ].…”
Section: Alcoholmentioning
confidence: 99%